1997
DOI: 10.1590/s0100-879x1997001200016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of estradiol benzoate on 5'-iodothyronine deiodinase activities in female rat anterior pituitary gland, liver and thyroid gland

Abstract: There is little information on the possible effects of estrogen on the activity of 5'-deiodinase (5'-ID), an enzyme responsible for the generation of T3, the biologically active thyroid hormone. In the present study, anterior pituitary sonicates or hepatic and thyroid microsomes from ovariectomized (OVX) rats treated or not with estradiol benzoate (EB, 0.7 or 14 µg/100 g body weight, sc, for 10 days) were assayed for type I 5'-ID (5'-ID-I) and type II 5'-ID (5'-ID-II, only in pituitary) activities. The 5'-ID a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
14
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
8
14
1
Order By: Relevance
“…Our results confirm that serum total T4 concentration is not altered by ovariectomy (Christianson et al 1981, Lisbôa et al 1997, but there is a small significant decrease in serum T3, also reported by Lima et al (2006). The hepatic, renal, thyroid, and pituitary D1 activities were unchanged in ovariectomized rats.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results confirm that serum total T4 concentration is not altered by ovariectomy (Christianson et al 1981, Lisbôa et al 1997, but there is a small significant decrease in serum T3, also reported by Lima et al (2006). The hepatic, renal, thyroid, and pituitary D1 activities were unchanged in ovariectomized rats.…”
Section: Discussionsupporting
confidence: 89%
“…Chen & Walfish (1978) and Lisbôa et al (1997) have reported that estradiol treatment of castrated females promotes an increase in serum TSH, but neither we nor Christianson et al (1981) found a similar increase in serum TSH.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Some previous reports indicate that estradiol might regulate thyroid function through a direct action on thyrocytes (34), apart from a possible effect on TSH secretion (35)(36)(37)(38). The administration of estradiol to ovariectomized and hypophysectomized rats leads to a higher thyroid radioiodide uptake (32,39), which supports the hypothesis of a direct effect of estrogen on the thyroid.…”
Section: Estrogensupporting
confidence: 72%
“…All the effects depended on dosage and length of the treatment period (Chen and Walfish, 1978;Boado et al, 1983). It has been demonstrated (Lisboa et al, 1997) that higher doses of estradiol strongly stimulate the activity of thyroid enzymes (5'-deiodinase) which are responsible for the generation of T 3 . In our experiments, the treatments with either silymarin, or E 2, increased the serum concentrations of all thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%